If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (9X) * cos(x) Multiply f * x fx = (9X) * cos(x) Remove parenthesis around (9X) fx = 9X * cos(x) Multiply X * cos fx = 9cosX * x Multiply cosX * x fx = 9cosxX Solving fx = 9cosxX Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 9cosX Simplifying f = 9cosX
| 5z+12=4z+5 | | (x^2-2)/2=7 | | 7(-3+6K)= | | 6+(-n)-7=-2 | | 3c-5c=9+4c | | 4x+5=1x+2 | | x/8-(-2)=-3 | | 61.2=6(m+3.6) | | 4w-6=3(w+1) | | 12x+2x=10x+20 | | (3x-2)-x=10 | | 6(y-1/3)=-1.2(2y-10) | | 12y-21/4= | | -x+6y=16 | | 20cosX=-31.3229 | | 8d+4=2d | | 2x+41=83 | | 5x^3+36x+7=0 | | -12y-6x=3 | | x(14x+31)+15=0 | | -7a-2b+7+2b+5a= | | 39,41=120,84 | | (8x-3)-(7x-4)+(-5x+6)= | | 4x^3+12x^2-72x-160=0 | | 7x-28y=35 | | 7x(6x+1)=511 | | 9x+63=8x+59 | | log(9x^2)-log(x)=2 | | 7x+8=3x-24 | | 11x-2=-24 | | combine(8x-3)-(7x-4)+(-5x+6)= | | 3y-2y=1 |